Influência da floresta ripária e do regime de chuvas na estrutura trófica de peixes em um riacho de mata Atlântica no Nordeste do Brasil - Luduvice, Jefferson Saulo da Vitória (2020)
The trophic ecology of the ichthyofauna in a stream may be related to the availability of resources in the environment, and this availability is influenced by factors such as the presence or absence of riparian forest, aquatic vegetation, fluvial regime, among others. In this context, the objective of this study was to test whether the rain regime and the presence of riparian forest influence the trophic structure of fish in an Atlantic Forest stream in Northeastern Brazil. For this purpose, fish from two stretches of the Tabocas stream (SE), one forested and the other deforested, were sampled bimonthly from March / 2018 to January / 2019. The fish were submitted to diet analysis and classified into five trophic guilds. Networks of interaction between consumers and resources were set up. A total of 682 specimens from 12 species were analyzed, nine native and three non-native (Hyphessobrycon eques, Poecilia reticulata and Xiphophorus maculatus). The species Hyphessobrycon parvellus, Compsura heterura, Poecilia reticulata, Astyanax fasciatus and Hyphessobrycon eques were the most abundant and frequent. 42 items were consumed grouped into 16 categories, with algae being the most frequent. The segregation of resources was verified among the analyzed species, indicating that the resources are limiting and the species tend to compartmentalize their niches. The congeners H. eques (non-native) and H. parvellus (native), for example, are both omnivorous, but have a low niche overlap. There was a predominance in the consumption of native items at both points and periods, although A. fasciatus has preferentially eaten allochthonous items in the forested point and in the rainy season. The deforested spot presented larger and more complex networks, probably due to the lack of shading, which results in higher primary productivity, capable of sustaining longer food chains. In relation to the periods, the rainy season presented the largest networks in relation to the dry period. Thus, the results indicate that both the presence of riparian forest and the rainfall regime influence the trophic structure of stream fish.